Ketahanan Lapangan Lima Genotipe Padi terhadap Penyakit Hawar Daun Bakteri - Rezki Heru Aditya; Wiwiek Sri Wahyuni; Paniman Ashna Mihardjo (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2015)
Bacterial leaf blight disease caused by Xanthomonas oryzae pv. oryzae is an important disease on rice in Indonesia. Four rice varieties, i.e. Inpari 30, Situbagendit, Luk-ulo and Cibogo has been known to have resistance to the disease. Therefore, they can be used as indicator plants to measure the resistance of any new rice genotypes to the disease. Research was aimed to evaluate field resistance of a new rice line, i.e. line X, with 4 resistant rice varieties as check control. The research was conducted in the field in Wirolegi villages, Sumbersari-Jember with natural infection of X. oryzae. Plant resistance was observed by measuring disease incidence (DI) and severity (DS). The highest DI (100%) was reached by all genotypes in different age. At 90 days after planting, DS of line X reached 11.85% which is far low compared to DS of var Situbagendit (40.25%). Based on DI and DS, line X is considered to have the best resistance to the disease, i.e. resistant in vegetative phase and moderately resistant in generative phase. However, the strain of X. oryzae infecting the plants in the field was unknown.